Development Of The 'Kasir-Risk' Prototype For Risk Mitigation In Primary Healthcare Integration Transformation - Ningsih, Kori Puspita; Sholeh, adkhan Sholeh; Rokhman, Nur Rokhman (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
The transformation towards Integrated Primary Healthcare (ILP) in Indonesia necessitates robust risk management to ensure service quality and patient safety. However, manual documentation and reporting at Community Health Centers (Puskesmas) hinder real-time risk response, creating a critical gap. This study aims to develop 'Kasir-Risk,' a digital prototype featuring an Early Warning System (EWS) dashboard, to mitigate risks and support accreditation standards. Employing a qualitative approach and prototyping method within the System Development Life Cycle (SDLC), this research involved 56 respondents from Puskesmas and the District Health Office of Bantul. Data was collected via Focus Group Discussions (FGD), observation, and documentation studies. The needs analysis revealed an urgent demand for an integrated tool for risk handling. The resulting Kasir-Risk application is a structured, secure, and data-driven system. Its design encompasses three main components: a functionality module for risk calculation and notifications, a user experience-based EWS dashboard, and a relational database. Built with modern technologies like Laravel, React.js, and MySQL, the prototype facilitates the entire risk management cycle—from identification and analysis to evaluation, mitigation, and reporting. This study concludes that Kasir-Risk serves as a viable digital solution for enhancing risk mitigation, real-time monitoring, and data-driven decision-making in primary healthcare transformation.